Prevalence and Multivariate Impact of Musculoskeletal Disorders on General Health, Occupational Fatigue, and Productivity in an Industrial Workforce - Choobineh, Alireza; Karami, Mohammad; Sahranavard, Yaser; Fakhraei, Mohammad Reza; Ghanbari Mohammad, Fatemeh; Alibeygian, Fatemeh; Hossainie Nasab, Somayeh; Alizadeh, Azam; Shahbazi, Mina; Tahmasebi, Reza (La Medicina del Lavoro, 2026)
Background: Musculoskeletal disorders represent a leading occupational health challenge in heavy‐industry settings, yet their combined impact on workers’ general health, fatigue, and productivity remains underexplored. This study aims to quantify the relationship between multisite musculoskeletal symptom burden and key health and performance outcomes among copper‐industry employees. Methods: A cross-sectional survey of 585 workers used the Standardized Nordic Musculoskeletal Questionnaire, the 28-item General Health Questionnaire, the SOFI-20 fatigue inventory, and the HPQ-26 productivity survey. Spearman’s rank correlation was used to examine bivariate relationships, and multivariable linear regression models adjusting generally for demographic, work-related, and psychosocial factors were employed to estimate the independent effect of the number of painful sites on health, fatigue, and productivity outcomes. Results: Fifty-seven percent of workers reported pain in at least one region during the preceding 12 months, with an average of 2.6 painful sites per person (standard deviation 2.4). The number of painful sites showed a moderate positive correlation with poorer general health scores (ρ = 0.43, p < 0.001) and higher fatigue scores (ρ = 0.53, p < 0.001), and a moderate negative correlation with productivity ratings (ρ = –0.30, p < 0.001). In adjusted regression analyses, each additional painful site was associated with a 1.9-point worsening in general health score (95% CI 1.5 to 2.2), an 8.4-point increase in fatigue score (95% CI 7.3 to 9.6), and a 1.6-point decrease in productivity score (95% CI –2.0 to –1.2), all with p-values < 0.001. Conclusions: There is a clear dose–response relationship between the number of painful anatomical sites and declines in health, increases in fatigue, and reductions in productivity among copper-industry workers. To address this multifaceted impact, interventions should integrate ergonomic workstation design, task rotation, optimized break schedules, and comprehensive health-promotion services targeting both physical and psychosocial risk factors.